Mathematical Communication Ability of High School Students in the Implementation of Experiental Learning Model - Triani, Nina Ayu; Mauladaniyati, Ratu; Sartika, Nenden Suciyati (S&Co Publishing, 2023)
The objective of this research is to determine whether the enhancement in mathematical communication skills of students instructed with the experiential learning model surpasses that of students instructed with the conventional learning model. This research is a quasi-experimental research design, with the research sample comprising one experimental class (utilizing the experiential learning model) and one control class (following the conventional approach), each consisting of 20 students. The research instrument employed is a descriptive test comprising a pretest and posttest. Based on the research data analyzed using the N-Gain hypothesis test, it can be concluded that there is an improvement in students' mathematical communication skills in the context of the three-variable linear equation system material. This improvement is more pronounced among students taught using the experiential learning model compared to those instructed using the conventional learning model.